The Role of Religious Moderation in Overcoming Bullying and Cyberbullying - Nafsyah Rizka Fitria; Mila Rizqi Ashari; Alisa Rahmawati; Amalia Arkana Putri; Hilmy Wahdi; Nafisah Nafisah (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Religious moderation can be interpreted as an approach that emphasizes a balance of tolerance, avoiding extremism in religion. Religious moderation plays an important role in overcoming bullying and cyberbullying behavior among teenagers. The research method used is literature research by collecting all data that is relevant to the research topic. The aim of this research is to look at the role of religious moderation in overcoming bullying and cyberbullying. The results of this research show that there are several strategies that can be implemented as an effort to prevent bullying and cyberbullying behavior, namely: emphasizing education, anti-bullying committees, campaigns for wise use of social media, dialogue between religious communities, and strengthening human values and justice so that creating a safe and harmonious life that is free from all acts of bullying and cyberbullying, especially those caused by differences in beliefs.